2006
DOI: 10.1017/s1041610205002929
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological interventions for aggressive behavior in older adults living in long-term care facilities

Abstract: Non-pharmacological interventions seem effective for managing AB. Future studies on the effectiveness of these interventions need to be more rigorous. Development in this field needs to be based on knowledge regarding the determinants of AB in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 37 publications
1
18
0
2
Order By: Relevance
“…Most previous systematic reviews of psychosocial treatments applied limited, if any, quality standards when selecting articles (Cohen-Mansfield, 2001;Snowden et al, 2003;Bharani and Snowden, 2005;Livingston et al, 2005;Turner, 2005;Landreville et al, 2006). Three reviews adopted a more discriminating approach, though not as rigorous as ours.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous systematic reviews of psychosocial treatments applied limited, if any, quality standards when selecting articles (Cohen-Mansfield, 2001;Snowden et al, 2003;Bharani and Snowden, 2005;Livingston et al, 2005;Turner, 2005;Landreville et al, 2006). Three reviews adopted a more discriminating approach, though not as rigorous as ours.…”
Section: Discussionmentioning
confidence: 99%
“…Several forms of non-pharmacological intervention have aimed to decrease the behavioral disturbances. Management of environment, training programs for caregivers, reminiscence psychotherapy directed toward the recognition of significant past situations, sensory stimulation, strategies to enhance appropriate behaviors, and psychosocial interventions have been common ways to reduce the suffering of patients and the burden on caregivers 47 . However, even in geriatric institutions, few studies have investigated exercise programs focused on behavioral disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Innovative and effective nonpharmacological treatments for depression and challenging behaviors have become more widespread in recent years (Camp, Cohen-Mansfield, & Capezuti, 2002;Landreville et al, 2006;Turner, 2005). In a comprehensive review, Opie, Doyle, and O'Connor (2002) concluded that there is evidence to support the efficacy of non-pharmacological interventions for behavioural disorders in dementia.…”
Section: Introductionmentioning
confidence: 99%
“…In a comprehensive review, Opie, Doyle, and O'Connor (2002) concluded that there is evidence to support the efficacy of non-pharmacological interventions for behavioural disorders in dementia. In a recent review of non-pharmacological interventions for aggressive behavior in older adults in long-term care, Landreville et al (2006) found that 66% of the studies reviewed showed a statistically significant reduction of aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation